Decompositions of Cubic Traceable Graphs - Liu Wenzhong; Li Panpan (Discussiones Mathematicae Graph Theory, 2020)
A traceable graph is a graph with a Hamilton path. The 3-Decomposition Conjecture states that every connected cubic graph can be decomposed into a spanning tree, a 2-regular graph and a matching. We prove the conjecture for cubic traceable graphs.